Kherson State University, Kherson, Ukraine MODERN TRENDS TO UPGRADE THE PROFESSIONAL TRAINING SYSTEM OF THE FUTURE MATHEMATICS TEACHER - Tatochenko, В. І.; Shypko , А. Л. (Journal of Information Technologies in Education (ITE), 2017)
An article devoted to the actual problem of professional pedagogical education - the modern tendencies of updating the system of professional training of the future teacher of mathematics. The relevance of the study is due to rapid changes in society, which involve making changes to the goal of preparing speech to life, which requires the teacher to transition from the knowledge model to the competent. This necessitates a fundamental need to rethink all the factors on which the quality of the educational process depends. In the article, based on the analysis of social production in societies of different types, the goal of general education at the stage of transition from industrial to postindustrial society is specified. The specified purpose explains the necessity of changes as a mathematical education in general educational institutions, as well as the system of professional training of teachers of mathematics. On the basis of the analysis of the state of the problem, a number of contradictions in the preparation of future mathematics teachers who will work in qualitatively new conditions of postindustrial information societies, which are characterized by rapid development and dynamism, is highlighted, the problem of preparing teachers for professional activity in a new, communicative environment, when the aging of information occurs faster than the educational cycle in an educational institution ends. The term "professional activity of the teacher of mathematics" is defined as a holistic purposeful complex open volatile dynamic pedagogical system, the functioning of which involves resistance to certain subsystems that ensure the readiness of students for effective pedagogical activity. The interconnection of subsystems on the basis of their integration allows achieving the main goal of the system - to prepare a competent teacher of mathematics. The functioning of such a system provides the creation of conditions for the development of the personality of the future teacher of mathematics on the basis of mastering the content of mathematical education, the operational-operational side of training, etc. Updating the methodology of future mathematics teachers is considered as an update to a set of five components: goals, content, methods, tools and organizational learning forms. The purpose of the updated methodical system is to form the future professional mathematics teachers of professional competence, which manifests itself in the ability to organize the processes of teaching mathematics at the level of modern requirements, the ability to successfully solve professional problems that arise in the learning process and are based on theoretical and practical readiness for learning pupils. The traditional content of the training of future teachers of mathematics has been updated taking into account the current stage of development of school mathematical education by including inclusion of a student in educational activity; designing student's educational activity as a step-by-step independent work; use of teaching methods that simulate the content of professional activity; development of competence-oriented programs, courses of professional disciplines, where each module adds a list of competencies (or competences) that are formed through its study; the reorientation to interdisciplinary and polyprofessionalism, as the environment in which the graduate will go, as well as the educational space itself. Elements of the content are modern professional approaches to the study of mathematics students, this content is mastered by students means education. At the present stage, active teaching methods are implemented within the framework of certain technologies, therefore, it is advisable to replace the methods, means, organizational forms of training with the structural component of the "learning technology". The use of training technology helps to simulate the content of future professional activities and to anticipate the active inclusion of students in learning activities, the dynamic movement of student activity from educational activities through quasi-professional and vocational-professional to professional activity; personal inclusion of a student in educational activity; designing student's educational activity as a step-by-step independent work; use of teaching methods that simulate the content of professional activity. The peculiarity of modern education system is that information space acts as its shell. Proceeding from this, there was a tendency to get the computer and educational virtual space of qualities of subjects of pedagogical process. In this connection, the place of NIT in the preparation of future teachers of mathematics is refined.